1938
DOI: 10.1002/cber.19380710523
|View full text |Cite
|
Sign up to set email alerts
|

Über hochpolymere Verbindungen, 191. Mitteil.: Über die Konstitution der Weizenstärke

Abstract: Nr. 5/1938] Staudinger, Husemann. 1057 169. H. Staudinger und E. Husemann: Uber hochpolymere Verbindungen, 191. Mitteil.l) : uber die Bonstitution der Weizenstibke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1941
1941
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…None gave values greater than about 200,000—still too small for starches that were predominately amylopectin. In 1938, Staudinger and Husemann [ 85 ] determined degrees of polymerization of starch fractions and rather correctly concluded that there exists not one starch molecule but a polymer homologous series and that differences in specific viscosities of different preparations owed to differences in the size of the macromolecules, not of molecular aggregates.…”
Section: The Molecules Of Starchesmentioning
confidence: 99%
“…None gave values greater than about 200,000—still too small for starches that were predominately amylopectin. In 1938, Staudinger and Husemann [ 85 ] determined degrees of polymerization of starch fractions and rather correctly concluded that there exists not one starch molecule but a polymer homologous series and that differences in specific viscosities of different preparations owed to differences in the size of the macromolecules, not of molecular aggregates.…”
Section: The Molecules Of Starchesmentioning
confidence: 99%